2020
DOI: 10.1590/1807-1929/agriambi.v24n1p37-43
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of peanut (Arachis hypogea) genotypes to salt stress in the initial phase

Abstract: This study aimed to evaluate the emergence, growth, biomass accumulation and tolerance of peanut genotypes under salt stress. The experiment was conducted in a protected environment (greenhouse), evaluating six peanut genotypes (Tatuí, L7151, Caiapó, IAC8112, IAC881 and Havana), which were subjected to two levels of irrigation water salinity (0.5 [control] and 3.5 dS m-1), arranged in a 6 x 2 factorial scheme, in a randomized block design, with five repetitions, with two plants per plot. Plants were cultivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…This reduction in the number of leaves may be associated with morphological strategies that the plant develops under stress conditions that induce reduced leaf expansion, causing stomatal closure, and the consequent reduction in the availability of CO 2 to the leaves (Silva Júnior et al, 2021;Sousa et al, 2021b). Comparable results to the present study were reported by Sá et al (2020), who evaluated genotypes of peanuts subjected to different levels of salinity, with a reduction in the number of leaves when saline levels increased.…”
Section: Resultssupporting
confidence: 68%
“…This reduction in the number of leaves may be associated with morphological strategies that the plant develops under stress conditions that induce reduced leaf expansion, causing stomatal closure, and the consequent reduction in the availability of CO 2 to the leaves (Silva Júnior et al, 2021;Sousa et al, 2021b). Comparable results to the present study were reported by Sá et al (2020), who evaluated genotypes of peanuts subjected to different levels of salinity, with a reduction in the number of leaves when saline levels increased.…”
Section: Resultssupporting
confidence: 68%
“…Peanut (Arachis hypogaea L.) is an oilseed crop of wide utilization as food, with high importance both in the socioeconomic sphere and in the food field not only in Brazil, but also in the world (SANTOS et al, 2012b;SÁ et al, 2020). According to an estimate by the National Supply Company (CONAB, 2020), the average yield of the peanut crop in Brazil, in 2020, was 3,564 kg ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Brazilian semi-arid region, cowpea is widely cultivated under rainfed conditions during raining periods and under irrigated conditions during the dry season, mainly in the irrigated perimeters of this region (Freitas et al, 2019). Irrigation in the semi-arid region is usually performed using saline water with high concentrations of sodium chloride salts (Medeiros et al, 2003;Sá et al, 2020). The use of saline water in agriculture poses high risks of salinization and environmental degradation of soils, since salinity is an environmental stress that limits crop yield, particularly in arid and semi-arid regions (Praxedes et al, 2010;Sá et al, 2017).…”
Section: Introductionmentioning
confidence: 99%